2021
DOI: 10.17582/journal.jahp/2021/9.3.213.221
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy Assessment of Avian Pasteurella multocida and Mycoplasma gallisepticum Local Vaccines

Abstract: | Diseases caused by Pasteurella multocida (P. multocida) and Mycoplasma gallisepticum (M. gallisepticum) are of significant importance and induce great losses in poultry industry, so vaccination against diseases caused by both organisms is crucial. The present study was conducted to prepare inactivated vaccines from local strains of P. multocida and M. gallisepticum either alone or in combinations, evaluate these vaccines through measuring the immune response as well as detect the protection rates against the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
0
0
Order By: Relevance
“…While protection % against P. multocida type "D" challenge was 80% in rabbit groups vaccinated with P. multocida vaccine and 90% for the combined one in comparison with 0% for control group. These findings were consistent with previous studies (Fatma Fathy 2018;El-Maghraby et al 2019;Ibrahim et al 2021) who found that P. multocida adjuvanted vaccines were more effective against challenge with virulent strains of P. multocida types A and D.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…While protection % against P. multocida type "D" challenge was 80% in rabbit groups vaccinated with P. multocida vaccine and 90% for the combined one in comparison with 0% for control group. These findings were consistent with previous studies (Fatma Fathy 2018;El-Maghraby et al 2019;Ibrahim et al 2021) who found that P. multocida adjuvanted vaccines were more effective against challenge with virulent strains of P. multocida types A and D.…”
Section: Resultssupporting
confidence: 93%
“…Also, Ibrahim et al (2021) concluded that the inactivated P. multocida Montanide adjuvanted vaccine gave long duration antibody titer when assessed by IHA test. Youssef and Tawfik (2011), when used the IHA test, found that inactivated rabbit Pasteurella vaccine adjuvanted with Montanide ISA-50 produced protective antibody titers against P. multocida and gave high and long-lasting antibody levels.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation